The entrepreneur constraints and quality performance in batik industry, Kuala Terengganu / Ain Natasha Abdullah , Nur Hazimah Ahmad and Nurul 'Atirah Md Isa - Abdullah, Ain Natasha; Ahmad, Nur Hazimah; Md Isa, Nurul 'Atirah (Faculty of Hotel and Tourism Management, 2015)
Batik handicraft is one of the oldest industries in Malaysia and contributes to the Malaysian economic well-being by first. The main purpose of this study is to identify the constraints to produce batik( towards Malaysian Tourism Industry. This study was carried out in the district of Kuala Terengganu, in the state of Terengganu, Malaysia and targeted the batik handicraft entrepreneur enterprise. The key findings reveal the batik entrepreneur evaluation about the constraints that arise in Kuala Terengganu and its effect to the batik quality performance. The findings from this research also reveal if there any relationship between the batik entrepreneur constraints which is the raw material constraint, labor constraint and capital and credit facilities constraint toward the batik quality performance.